Konflik Sosial dalam Novel Tamu karya Wisran Hadi - Meiji Syahrul; Muhammad Ismail Nasution (Persona: Kajian Bahasa dan Sastra, 2023)
This research aims to identify: (1) the form of social conflict in the novel Tamu by Wisran Hadi, (2) the cause of social conflict in the novel Tamu by Wisran Hadi, (3) the impact of social conflict in the novel Tamu by Wisran Hadi. The object used in this research is the novel Tamu by Wisran Hadi published in 2002. The method used in this research is descriptive method. The data taken in this study are words, phrases, clauses and sentences related to the form, cause, and impact of social conflict in the novel Tamu by Wisran Hadi. The instrumental used in this research is the writer himself by using the help of other instruments in the form of recording sheets. The technique of data collection used is reading and understanding the novel, determining the main character, and searching and recording data related to the research problem contained in the novel. Analyzing data techniques used are identifying and classifying data. Next, interpret the data, and conclude the data analysis. The results of the study mention (1) the form of social conflict in the novel Tamu by Wisran Hadi in the form of personal conflict, group conflict, and conflict in society. (2) the causes of social conflict in the novel Tamu by Wisran Hadi are caused by differences between individuals or individuals, differences in social class, differences in interests, and social change. (3) the impact of social conflict in the novel Tamu by Wisran Hadi includes the destruction of group unity, personality change, and the destruction of social values and norms.